Biofuel from vegetable oil sludge by pyrolysis process. - Son, Van Dinh; Nam, Le Thi Hoai (Vietnam Journal of Chemistry, 2012)
The product distribution obtained from the pyrolysis of vegetable oil sludge was studied at atmospheric pressure in a fixed-bed reactor at 600oC. The experiment shows that vegetable oil sludge conversion was 74.03% by pyrolysis process. The dry gas formation of the gas is 9.4% and LPG is 16.96% and coke is 18.97%.  The liquid products of the pyrolysis process have a large boiling range and it cover the range of gasoline fraction (28.78%), LCO (approximately 13.70%) and HCO (12.27%).